New developments with the INSU/Météo VHF radar at CNRM/Toulouse — RASS, FDI and upgraded processing techniques - Vladislav Klaus; Jean-Pierre Aubagnac; Joël Van Baelen; Guy Chérel; Roger Durbe; Alain Frappier (Meteorologische Zeitschrift, 1998)
The goal of this contribution is to present the latest developments performed with the VHF wind profiler at the Centre National de Recherches Météorologiques (CNRM) in Toulouse. The current work includes a radio acoustic sounding system (RASS) capability to measure virtual temperature profiles in the mid troposphere, frequency domain interferometry (FDI) to study the advent of thin scattering laminae, and possibly new signal processing approaches such as wavelet transforms to filter signals perturbed by planes and other spurious echoes. The technical aspects as well as the performance assessments of the system are discussed.